Investigation of site properties in Adapazari, Turkey, using microtremors and surface waves - Silahtar, Ali; Budakoglu, Emrah; Horasan, Gunduz; Yıldırım, Eray; Kuyuk, H. Serdar; Yavuz, Evrim (Springer, 2016)
Determination of suitable areas for new residential buildings is crucial to increase the resilience of buildings against earthquake hazards. After the 1999 Izmit earthquake M-w 7.4, the city of Sakarya has been expanding rapidly in terms of both the population and number of superstructures. Despite the fact that Sakarya suffered several large earthquakes in the last two decades, the geophysical properties of the region have not been adequately investigated. In this study, the site properties of Sakarya University, Esentepe Campus, and its surrounding Serdivan district, which is one of the important parts of the city, are determined using microtremor measurements and surface wave analysis. Nakamura's spectral ratio method (spectral ratio between the horizontal and vertical components, H/V or HVSR) was used to determine the fundamental frequency and site amplification values. The shear wave velocity profiles of the studied sites were determined using the multichannel analysis of surface waves method. Seismic measurements were performed at 34 locations to record the surface waves in the area. The fundamental frequency and site amplification values are determined as 1.02-11.68 and 1.33-5.96 Hz, respectively, from the microtremor measurements. The fundamental frequency is between 4.0 and 11.5 Hz in the campus area and between 1.3 and 2.0 Hz near the D-100 intercity highway. The site amplification was determined to be 1-2.5 in the campus area. The greatest site amplification (6) is obtained at thick alluvium deposits in the valley between hills. The average shear wave velocity values are within the range of 300 and 1120 m/s. Some parts located on the hill area have better soil condition (B) categories, according to the National Earthquake Hazard Reduction Program, and have comparatively high shear wave velocities in the range of 740-1080 m/s, whereas low velocity values are found at the thick alluvium deposits (D). We found that the geological properties and topographies play very important roles on the shear wave velocity and the amplification factors in the investigated area.
Keywords: Microtremor; Surface waves; V(s)30; Adapazari